Analisis Kesalahan Siswa Dalam Menyelesaiakan Soal Cerita Pokok Pembahasan Teorema Pythagoras - Bete, Maria Erlince; Amsikan, Stanislaus; Simarmata, Justin Eduardo (MATH-EDU: Jurnal Ilmu Pendidikan Matematika, 2023)
The aims of this study was to determine the type of percentage of errors made by students in solving story problems in the Pythagorean theorem material of grade VIII SMPN 2 Insana based on Newman's procedure, knowing the factors causing student errors in solving story problems in the Pythagorean theorem of grade VIII SMPN 2 Insana. This study is a qualitative description research. The subjects in this study were 20 students of SMPN 2 Insana Class VIII. Data collection using the written test method in the form of three question numbers and interviews. The results of this study showed that reading errors 13%, understanding errors 37%, transformation errors 39%, completion process errors 15%, answer writing errors 23%.